Positioning of ROV at station ODEN_AO2018_821-1 - Anhaus, Philipp; Katlein, Christian; Hoppmann, Mario; Nicolaus, Marcel (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2020)
Along with the radiation measurements, ROV positions were obtained from acoustic LBL (Long BaseLine)-positioning and all parameters of vehicle depth, distance to the ice and attitude recorded. All times are given in UTC.